2012
DOI: 10.2967/jnumed.110.083386
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PET of Human Urokinase-Type Plasminogen Activator Receptor with 64Cu-DOTA-AE105: Implications for Visualizing Cancer Invasion

Abstract: Expression levels of the urokinase-type plasminogen activator receptor (uPAR) represent an established biomarker for poor prognosis in a variety of human cancers. The objective of the present study was to explore whether noninvasive PET can be used to perform a quantitative assessment of expression levels of uPAR across different human cancer xenograft models in mice and to illustrate the clinical potential of uPAR PET in future settings for individualized therapy. Methods: To accomplish our objective, a linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 35 publications
6
82
1
Order By: Relevance
“…Accordingly, we have for several years focused on development of radioligands based on the high-affinity peptide antagonist AE105 for PET imaging of uPAR expression (12)(13)(14)(15)(16)(17). We recently published results from a promising first-in-human study with 64 Cu-DOTA-AE105 showing high uptake in both primary tumor lesions and lymph node metastases paralleled with high uPAR expression in excised tumor tissue, thereby providing evidence for uPAR PET imaging in cancer patients (4).…”
mentioning
confidence: 99%
“…Accordingly, we have for several years focused on development of radioligands based on the high-affinity peptide antagonist AE105 for PET imaging of uPAR expression (12)(13)(14)(15)(16)(17). We recently published results from a promising first-in-human study with 64 Cu-DOTA-AE105 showing high uptake in both primary tumor lesions and lymph node metastases paralleled with high uPAR expression in excised tumor tissue, thereby providing evidence for uPAR PET imaging in cancer patients (4).…”
mentioning
confidence: 99%
“…Previous studies investigated the use of a high-affinity 9-mer peptide antagonist of the uPA-uPAR (AE105) for positron emission tomography (PET) imaging of uPAR expression, and showed that copper-64 ( 64 Cu)-labeled DOTA-AE105 exhibited specific and high-affinity binding to uPAR in vitro and in vivo (16)(17)(18). However, the clinical application of this protocol is restricted due to the limited availability of 64 Cu and the high cost of PET imaging.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the Kjaer group performed a series of important steps to modify and characterize radioactive uPAR ligands. They developed and examined the radioactive uPAR ligands 68 Ga-DOTA-AE105-NH 2 (14), 68 Ga-NODAGA-AE105-NH 2 (14), 18 F-AlF-NOTA-AE105 (15), 64 Cu-CB-TE2A-PA-AE105 (16), and 64 Cu-DOTA-AE105 (17). In this issue of The Journal of Nuclear Medicine, Persson et al from the Kjaer group present evidence of the usefulness of two new uPAR PET tracers, 64 Cu-NOTA-AE105 and 68 Ga-NOTA-AE105, in glioblastoma imaging (18).…”
Section: See Page 272mentioning
confidence: 99%